The Epidemiology and Risk Factor of Lymphatic Filariasis Strains of Wuchereria Bancrofti in Indonesia - Masriadi, Masriadi (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
a